Stunting Detection System and Nutritional Status of Toddlers using Anthropometric Index and Body Mass Index - Karsana, I Wayan Widi; Andhika Kurniawijaya, Putu; Resty Wasita, Rai Riska (Fakultas Sains dan Teknologi, Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The stunting problem in Indonesia is a problem that has become a national concern. The target of reducing stunting in 2024 is 14%, while in 2022 it is still at 24%. Various efforts to deal with stunting have been carried out by the Indonesian government at both the central and local government levels but have not been able to reduce stunting significantly. To conduct early detection of stunting in toddlers, one can use anthropometric index data as a reference and body mass index for nutritional status in toddlers. Parameters in the anthropometric index use height by age or body length by age, while the body mass index uses body weight and height as indicators. This study aims to develop a stunting detection system and nutritional status of toddlers using anthropometric indices and body mass index and validate the comparison of system output results with the results of manual calculations with standard formulas from the Ministry of Health of the Republic of Indonesia. The research found that there is a match between the results of manual calculations and calculations from the developed system, or, in other words, it can be concluded that there is a valid influence of nutritional status on the potential for stunting in toddlers.